PENYAKIT MALARIA DAN MEKANISME KERJA OBAT-OBAT ANTIMALARIA - Muti’ah, Roihatul (ALCHEMY, 2012)
Malariais one of theinfectious diseaseis stillaproblem ofthe world withhigh mortality. Therapeutic purpose of uncomplicated malariais to eliminateplasmodiumcause infection to preventinfectionseverity, complications andbreak the chain oftransmission. While the purpose therapyof severemalaria is to prevent mortality.Recommendedtherapy of malaria isa combination of twoormore antimalarial drugsthat mechanisms actionkillsmalarialparasitesin thebloodand theamount of each drugworks ondifferent receptors. The use ofa combination ofseveralantimalarial drugshas becomea necessityforprevention ofmalariaparasitestrainsthat are resistantto certain drugs. Combination therapyinclude:ACTs(artemisinin combinationtherapies); artesunateandamodiaquin; artesunateandmefloquin; artesunatewith oneof theSP, lumefantrin, piperaquin, pyronaridin; antibiotic(doxyciclin, clindamycine, azithromycin), artemether-lumefantrine (AL); chloroquineandSP;atovaquoneandproguanil (Malarone)